Community Empowerment through Sustainable Straw Mushroom Cultivation Using Oil Palm Waste - Sri Astuti; Sarono; Supriyanto; Joko Wibowo; Brando Luiffan Hutasoit (PT. Altaf Publishing Corp, 2026)
This community service program was implemented to empower straw mushroom producer groups in Kalisari Village, Kalirejo District, Central Lampung, through the utilization of empty oil palm fruit bunches (tankos) as a sustainable growing medium. The program focused on the application of Simple Patent No. IDS000005809 to improve straw mushroom productivity using tankos and to convert post-harvest mushroom waste into value-added organic compost. The implementation strategy combined technology socialization, hands-on training, field demonstrations, and continuous technical assistance throughout the production cycle.The results demonstrated a substantial improvement in the technical capacity of group members, with 100% of participants successfully mastering the application of the patented cultivation technology. Straw mushroom productivity increased significantly, with biological efficiency rising from 4.11% to 7.71%, representing an improvement of 3.60 percentage points compared to pre-intervention conditions. In addition, 78% of participants were able to independently process spent mushroom growing media into organic compost. Overall, the program generated positive economic, social, and environmental impacts, contributing to increased farmer income, improved waste management, and the promotion of sustainable and circular agribusiness practices within the local community.